A systematic review of the literature on survey questionnaires to assess self-medication practices - Limaye, Dnyanesh; Limaye, Vaidehi; Krause, Gerard; Fortwengel, Gerhard (International Journal Of Community Medicine And Public Health, 2017)
Self-medication is of great public health importance as it often bypasses regulatory mechanisms to assure quality of health care. Nevertheless there are no established standards on how to assess self-medication. We therefore intended to systematically retrieve questionnaires and survey tools used to capture self-medication, with the aim to identify the scope of information investigated in this context and commonalities between the tools. We conducted a systematic review of the literature on questionnaires used for self-medication assessment by searching PubMed and Web of Science databases using the combinations of following keywords; self-medication, self-prescription, non-prescription, questionnaire. Truncation was used to ensure retrieval of all possible variations of search terms. The search was limited to articles published between 1st January 2000 and 31st December 2015, human studies and English language. Duplicate and irrelevant studies were excluded from the final review. A total of 158 studies were included in the review. Studies were from diverse geographical locations, most of the studies were from Nigeria 16 (10.1%) followed by India 10 (6.3%) and Iran 8 (5%). Forty-three studies (27.2%) focused on antibiotic self-medication. Majority of the studies (106; 67%) were done with adult populations. The components addressed by the questionnaires covered: reasons for self-medications in 147 (93%) studies, purchasing source in 136 (86%) studies, medical conditions to be treated in 153 (96.8%) studies, adverse events in 67 (42.4%) studies, use of prescribing information in 24 (15.1%) studies and antibiotic resistance awareness in 20 (46.5%) antibiotic studies. For 74 (46.8%) studies, survey questionnaires were self-administered and most studies (57; 36%) were done at homes of respondents. Thirty-seven (23.4%) studies did not report any recall period for self-medication practices. Study response rates varied from 17.9% to 100%, and while validity of the study questionnaire was reported for 100 (63.3%) studies, 15 (9.5%) studies reported reliability test of the study questionnaire. There is a large variety of questionnaires being used for investigating self-medication practices making comparability and meta-analyses very difficult. It is desirable to have a basic set of standardized survey questions on this topic to make available for future research groups in this field.